Contraceptive Method Switching and Long-Acting Reversible Contraception Removal in U.S. Safety Net Clinics, 2016-2021 - Darney, Blair G; Biel, Frances M; Oakley, Jee; Coleman-Minahan, Kate; Cottrell, Erika K (Obstetrics and gynecology (New York. 1953), 2023)
To describe patterns of contraceptive method switching and long-acting reversible contraception (LARC) removal in a large network of community health centers. We conducted a retrospective cohort study using individual-level electronic health record data from 489 clinics in 20 states from 2016 to 2021. We used logistic regression models, including individual-, clinic-, and state-level covariates, to calculate adjusted odds ratios and predicted probabilities of any observed contraceptive method switching and LARC removal among those with baseline incident LARC, both over 4-year time periods. Among 151,786 patients with 513,753 contraceptive encounters, 22.1% switched to another method at least once over the 4-year observation period, and switching patterns were varied. In patients with baseline LARC, the adjusted predicted probability of switching was 19.0% (95% CI 18.0-20.0%) compared with patients with baseline moderately effective methods (16.2%, 95% CI 15.1-17.3%). The adjusted predicted probability of switching was highest among the youngest group (28.6%, 95% CI 25.8-31.6% in patients aged 12-14 years) and decreased in a dose-response relationship by age to 8.4% (95% CI 7.4-9.4%) among patients aged 45-49 years. Latina and Black race and ethnicity, public or no insurance, and baseline Title X clinic status were all associated with higher odds of switching at least once. Among baseline LARC users, 19.4% had a removal (to switch or discontinue) within 1 year and 30.1% within 4 years; 97.6% of clinics that provided LARC also had evidence of a removal. Community health centers provide access to method switching and LARC removal. Contraceptive switching and LARC removal are common, and clinicians should normalize switching and LARC removal among patients.